(untitled) (Research, Society and Development, 2025)
Introduction: Neurodegenerative disorders, such as Parkinson’s Disease (PD), have become a growing burden worldwide. PD is characterized by the death of dopaminergic neurons and the presence of Lewy bodies, resulting in motor symptoms. The endocannabinoid system has attracted attention due to its neuroprotective potential, especially with the use of cannabinoid compounds such as THC and CBD. Objective: To analyze the clinical use of THC and CBD in the treatment of patients with PD, investigating the effects on motor symptoms, quality of life and possible adverse effects. Methodology: An integrative literature review was performed, using articles from 2014 to 2025. Results and Discussion: The use of CBD has shown modest effects in improving quality of life and reducing anxiety, but did not significantly impact motor symptoms. The impact of CBD on sleep was positive in terms of satisfaction, but without changes in REM sleep disorders. The combination of CBD and THC, on the other hand, has produced adverse effects, such as dizziness and difficulty concentrating, without clear benefits. Studies suggest that the endocannabinoid system may modulate synaptic functions, but the long-term effects are still uncertain. Conclusion: Although CBD shows some potential to improve quality of life and reduce anxiety, its effects on motor and cognitive symptoms are inconclusive. The combination of THC and CBD should be used with caution, and more controlled research is needed to assess the long-term efficacy and safety of these substances in the treatment of PD.